2022
DOI: 10.15294/jpfi.v18i1.28924
|View full text |Cite
|
Sign up to set email alerts
|

Development of Physics E-book Based on Technological Pedagogical Content Knowledge (TPACK) on Thermodynamic Laws Topic

Abstract: This research was developmental research with aims to develop, knowing validity and practicability of thermodynamics e-book based on TPACK. This research was using 4D models and did only as far as develop step. The result based on 4D model steps were (1) Define produces task analysis to fulfil 21st century skill, (2) Design produces 2 product which are teacher book and student book, (3) Develop step produces result of validation and the last product (e-book/flipbook for teacher and student). Expert validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…PCK is used to understand the interaction of teachers' knowledge and practices and knowledge for planning to teach a particular topic to improve student outcomes in a particular way, for a particular purpose, and for a particular student. Core was used to conceptualize PCK in this way (Baihaqi et al, 2022).…”
Section: B Product Practicalitymentioning
confidence: 99%
“…PCK is used to understand the interaction of teachers' knowledge and practices and knowledge for planning to teach a particular topic to improve student outcomes in a particular way, for a particular purpose, and for a particular student. Core was used to conceptualize PCK in this way (Baihaqi et al, 2022).…”
Section: B Product Practicalitymentioning
confidence: 99%
“…E-modules can stimulate Students' curiosity (Syafril, 2021), subsequently encouraging their direct involvement in various learning activities (Aarsand, 2019). Therefore, e-modules are suitable for various levels of education and subjects, including physics (Haruna, 2021;Baihaqi, 2022). Furthermore, e-modules can be developed using various approaches, one of which is the Creative Problem Solving (CPS) model.…”
Section: Introductionmentioning
confidence: 99%
“…Baihaqi et al's research revealed that the use of TPACK-based e-books in physics classes was deemed legitimate, with an average score of 3,88[9]. With an average score of 3,26, Siregar, Kairuddin, and Mansyur's other study demonstrated that the use of TPACK-based E-books was deemed legitimate[10].…”
mentioning
confidence: 99%